Technique for Fattening Mand Crab (Scylla serrata) Using the Apartement System at CV. Istana Kepiting, District Bone - Aqza, Darul; Sektiana, Sinar Pagi; Raharjo, Sinung (Jurnal Media Akuakultur Indonesia, 2023)
Efforts to fatten Mangrove Crabs, still need to be developed because Mangrove Crabs from fishermen's catches, their bodies are less contained, weight becomes less attractive to consumers, so the economic value decreases. Therefore, the author chose the title Mangrove Crab Fattening Technique (Scylla Serrata) Using Apartment System and Financial Analysis at Cv.Istana Crab, Kab.Bone, South Sulawesi. With the aim of evaluating the technical aspects of fattening Mangrove Crab (S.serrata) by using the Apartment system. Evaluating the fattening cultivation performance of Mangrove Crabs (S.serrata) by using the Apartment system by showing good live growth rate results with Avirage Daily Growt (ADG) of 2-3 g / day. Analyzing the financial aspects of fattening Mangrove Crab (S.serrata) by using the Apartment system with a total profit in one year of Rp.45,420. Identifying problems and compiling proposals for mangrove crab fattening interventions (S.serrata) by using the Apartment system with the Fishbone analysis method there are several factors that are the problem of not achieving SR targe in the company including human factors (Man) that lack discipline, methods (Methods) that are not good in handling and controlling water quality, tools (Machines) that still have some tools less than capacity, and materials (Materials) that need to be selected for good and healthy seeds based on company goals.